2019
DOI: 10.1371/journal.pone.0209398
|View full text |Cite
|
Sign up to set email alerts
|

The importance of assigning responsibility during evaluation in order to increase student satisfaction from physical education classes: A structural equation model

Abstract: Considering the benefits that students report when evaluating physical education classes, the purpose of the present study was to analyse the relationships between the assignment of student responsibility in the evaluation, motivational variables and the satisfaction with the physical education classes, using The Theory of Self-determination as a support method. The sample for this study was 922 students, of both genres and in Compulsory Secondary Education, aged between 14 and 18 years. To carry out the study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 73 publications
0
7
1
1
Order By: Relevance
“…Así mismo, cuando los estudiantes afrontan clases en las que adquieren nuevas habilidades de forma efectiva, obteniendo reconocimiento social es cuando muestran mayores índices de satisfacción y menores de aburrimiento, mientras que cuando se evita la mejora individual, los resultados se tornan (Baños & Arrayales, 2019). En relación a lo anterior, el profesorado tiene un papel fundamental, ya que tiene en sus manos la opción de llevar a cabo una metodología que favorezca la autonomía (Salazar-Ayala & Gastélum-Cuadras, 2020) e incluir contenidos novedosos (Aibar et al, 2021;González-Cutre & Sicilia, 2019), e incluso asignar responsabilidades en las evaluaciones (asumiendo los riesgos en los resultados) (Leyton-Román et al, 2019), proporcionando una mayor satisfacción que repercutirá positivamente en el rendimiento académico (Baños et al, 2017(Baños et al, , 2018a(Baños et al, , 2020.…”
Section: Introductionunclassified
“…Así mismo, cuando los estudiantes afrontan clases en las que adquieren nuevas habilidades de forma efectiva, obteniendo reconocimiento social es cuando muestran mayores índices de satisfacción y menores de aburrimiento, mientras que cuando se evita la mejora individual, los resultados se tornan (Baños & Arrayales, 2019). En relación a lo anterior, el profesorado tiene un papel fundamental, ya que tiene en sus manos la opción de llevar a cabo una metodología que favorezca la autonomía (Salazar-Ayala & Gastélum-Cuadras, 2020) e incluir contenidos novedosos (Aibar et al, 2021;González-Cutre & Sicilia, 2019), e incluso asignar responsabilidades en las evaluaciones (asumiendo los riesgos en los resultados) (Leyton-Román et al, 2019), proporcionando una mayor satisfacción que repercutirá positivamente en el rendimiento académico (Baños et al, 2017(Baños et al, , 2018a(Baños et al, , 2020.…”
Section: Introductionunclassified
“…From the psychological perspective, the sense of social responsibility refers to a relatively stable psychological quality of individuals who actively undertake social responsibility or help others, which has important practical significance ( Huang et al, 2016 ). Previous studies have shown that the sense of responsibility is an effective predictor of a series of positive psychology characteristics and behaviors, such as job performance, academic achievement, sound development of personality, positive self-evaluation, attitude toward setbacks and failures, and altruistic behavior ( Wentzel, 1991 ; Leyton Román et al, 2019 ; Otto et al, 2022 ; Rajasekar et al, 2022 ; Scholten et al, 2022 ; Zyuzev, 2022 ). Scholars have confirmed the influence of fathers’ presence on teenagers’ social responsibility.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…Assessment is essential to education (Loyd & Koenig, 2008;Blake & Muttock, 2012;Leyton Román et al, 2019). It is the daily business in education prevailing in different forms, purposes and levels (Huber & Skedsmo, 2016).…”
Section: Assessment In Education Before and During The Pandemicmentioning
confidence: 99%